Exploring the social ties and diversity in the incarceration experience of Hispanic/Latino/Spanish individuals - Montes, Andrea N. (Journal of ethnicity in criminal justice, 2023)
The study starts by examining descriptive differences between incarcerated Hispanic/Latino/Spanish subgroups. Then, using three measures of social ties as dependent variables, explores whether using Hispanic/Latino/Spanish subgroup categories, as compared to a single category, reveals otherwise obscured differences. Compared to other subgroups Mexicans had a higher percentage of males and married individuals, and a lower percentage of individuals who were previously arrested. Puerto Rican/other Caribbeans had a higher percentage who were 29 years or younger. Regression analyses (N = 5,967) showed that before incorporating controls, Mexican individuals, compared to White individuals, had a higher likelihood of receiving letters or making calls. Collectively, these results underscore the need for further understanding ethnic identity and how this identity is associated with criminological experiences and outcomes.